MODERNIZATION OF THE UZBEKISTAN STOCK MARKET BASED ON FINTECH AND DIGITAL TECHNOLOGIES - A. Ibodullayev (European Science Publishing, 2025)
This article analyzes the changes resulting from the implementation of financial technologies (FinTech) and digital platforms in the securities market of the Republic of Uzbekistan. The introduction of FinTech technologies, particularly automation and digital identification systems, has improved operational efficiency and contributed to ensuring market transparency and security. Additionally, regulatory updates have further enhanced the positive impact of FinTech solutions on the market. The research findings demonstrate the success of digital transformation in the Uzbek securities market and provide a scientific basis for the future development of the market based on innovative technologies.
Keywords: FinTech, digital platforms, securities market, Uzbekistan, automation, digital identification, regulatory updates, operational efficiency, transparency, security.